Design procedure to convert a maximum power point tracking algorithm into a loop control system - de Brito, Moacyr A. G.; Prado, Victor A.; Batista, Edson A.; Alves, Marcos G.; Canesin, Carlos A. [UNESP] (MDPI, 2021)
This paper presents a novel complete design procedure to convert a maximum power point tracking (MPPT) algorithm into a control system. The MPPT algorithm can be tuned by employing any control system design. In this paper, we adopted Bode diagrams using the criteria of module and phase as the power electronics specialists are habituated with such concepts. The MPPT control transfer functions were derived using the average state equations and small-signal analysis. The control loops were derived for power and voltage control loops. The design procedure was applied to the well-known perturb and observe (P&O) and incremental conductance (IC) algorithms, returning the P&O based on PI and IC based on PI algorithms. Such algorithms were evaluated through simulation and experimental results. Additionally, we showed that the proposed design methodology can optimize energy harvesting, allowing algorithms to have outstanding tracking factors (above 99%) and adaptability characteristics.
Keywords: Algorithms; Control loops; Energy harvesting; MPPT; Photovoltaic energy